Navigating complexity: a comprehensive review of microcatheter shaping techniques in endovascular aneurysm embolization - Liu, Changya; Wu, Xinxin; Hu, Xuebin; Wu, Linguangjin; Guo, Kaikai; Zhou, Shuang; Fang, Bangjiang (Frontiers in Neurology, 2023)
The endovascular intervention technique has gained prominence in the treatment of intracranial aneurysms due to its minimal invasiveness and shorter recovery time. A critical step of the intervention is the shaping of the microcatheter, which ensures its accurate placement and stability within the aneurysm sac. This is vital for enhancing coil placement and minimizing the risk of catheter kickback during the coiling process. Currently, microcatheter shaping is primarily reliant on the operator's experience, who shapes them based on the curvature of the target vessel and aneurysm location, utilizing 3D rotational angiography or CT angiography. Some researchers have documented their experiences with conventional shaping methods. Additionally, some scholars have explored auxiliary techniques such as 3D printing and computer simulations to facilitate microcatheter shaping. However, the shaping of microcatheters can still pose challenges, especially in cases with complex anatomical structures or very small aneurysms, and even experienced operators may encounter difficulties, and there has been a lack of a holistic summary of microcatheter shaping techniques in the literature. In this article, we present a review of the literature from 1994 to 2023 on microcatheter shaping techniques in endovascular aneurysm embolization. Our review aims to present a thorough overview of the various experiences and techniques shared by researchers over the last 3 decades, provides an analysis of shaping methods, and serves as an invaluable resource for both novice and experienced practitioners, highlighting the significance of understanding and mastering this technique for successful endovascular intervention in intracranial aneurysms.